Impact of Sedentary Life Style on Anthropometric and Cardiovascular Parameters - Jayalakshmi, M. K.; Raj, N. Prabhu; Shanmukhappa, N. J.; Johncy, S. Smilee (Highlights on Medicine and Medical Research Vol. 13, 2021)
Aims: Physical inactivity is increasing among people of all ages in both developed and developing countries, due to an increase in sedentary lifestyles paired with an increase in the use of technology in daily life. A sedentary lifestyle contributes to a developing physical activity gap, or an imbalance between the requirement for and realisation of physical activity required for optimum health and functional ability. As a result, the purpose of this study was to observe the differences in specific anthropometric and cardiovascular parameters between sedentary and non-sedentary female individuals aged 25 to 55 years. Methods: A total of 105 healthy female individuals were chosen at random from the Davangere city. Out of which 47 were sedentary and 58 were non-sedentary subjects. Anthropometric parameters such as weight, height, body mass index, waist circumference, hip circumference, waist to hip ratio were assessed. Cardiovascular parameters such as pulse rate, blood pressure were also assessed. Results: Sedentary subjects had statistically significant increases in anthropometric and cardiovascular parameters as compared to non-sedentary subjects in our study. Conclusion: Low levels of physical activity are linked to an increased risk of weight gain and a significant increase in blood pressure, according to this review. Although our study is by no means exhaustive, it provides a glimpse into the variety of adaptations /alterations in anthropometric parameters that occurs due to sedentary life style, even in the absence of overt disease. The anthropometric and cardiovascular parameters were increased in sedentary subjects but there was statistically significant increase after the age of 35 years.